Transformation and gene-disruption in the apple-pathogen, Neonectria ditissima - Heriberto Vélëz; Jonas Skytte af Sätra; Firuz Odilbekov; Salim Bourras; Larisa Garkava-Gustavsson; Kerstin Dalman (Hereditas, 2022)
Abstract Background Apple production in Sweden and elsewhere is being threatened by the fungus, Neonectria ditissima, which causes a disease known as European canker. The disease can cause extensive damage and the removal of diseased wood and heavily infected trees can be laborious and expensive. Currently, there is no way to eradicate the fungus from infected trees and our knowledge of the infection process is limited. Thus, to target and modify genes efficiently, the genetic transformation technique developed for N. ditissima back in 2003 was modified. Results The original protocol from 2003 was upgraded to use enzymes currently available in the market for making protoplasts. The protoplasts were viable, able to uptake foreign DNA, and able to regenerate back into a mycelial colony, either as targeted gene-disruption mutants or as ectopic mutants expressing the green fluorescent protein (GFP). Conclusions A new genetic transformation protocol has been established and the inclusion of hydroxyurea in the buffer during the protoplast-generation step greatly increased the creation of knockout mutants via homologous recombination. Pathogenicity assays using the GFP-mutants showed that the mutants were able to infect the host and cause disease.